2003
DOI: 10.1540/jsmr.39.55
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nifedipine and Nickel on Plateau Potentials Generated in Submucosal Interstitial Cells Distributed in the Mouse Proximal Colon.

Abstract: The effects of nifedipine and nickel ions (Ni 2+ ), known inhibitors of L-and T-type voltage-gated Ca-channels respectively, were investigated on plateau potentials recorded from submucosal interstitial cells distributed in the mouse proximal colon. Plateau potentials were generated at a frequency of about 15 times min -1 and were formed of two components. The primary component had an initial fast rate of rise with a transient potential (rate of rise, 130 mV/s; peak amplitude, 35 mV) and was followed by a seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…This is consistent with the hypothesis that the pacemaker responsible for HF contractions is the ICC network located at the submucosal border. Moreover, it has been recently reported that in the mouse colon near the submucosa, c‐kit positive cells generate ‘plateau potentials’ at a frequency of about 15 min −1 27,33 . These plateau potentials are very similar in frequency to the slow wave activity previously described in the rat colon 24 and are responsible for HF contractions described all along the colon in the present work.…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with the hypothesis that the pacemaker responsible for HF contractions is the ICC network located at the submucosal border. Moreover, it has been recently reported that in the mouse colon near the submucosa, c‐kit positive cells generate ‘plateau potentials’ at a frequency of about 15 min −1 27,33 . These plateau potentials are very similar in frequency to the slow wave activity previously described in the rat colon 24 and are responsible for HF contractions described all along the colon in the present work.…”
Section: Discussionsupporting
confidence: 85%
“…We, therefore, would like to propose that in the proximal colon of the guinea-pig, there is a population of nitrergic nerves whose cell bodies are located in the submucosal layer, that receive cholinergic inputs and which send axons to circular smooth muscle cells. The proximal colon is rich in ICC-SMP (Kobayashi et al, 1995;Kobayashi et al, 1996;Nahar et al, 1998;Pluja et al, 2001), and these cells periodically generate plateau-type action potentials (Yoneda et al, 2002;Yoneda et al, 2003;Hotta et al, 2005). While the physiological functions of ICC-SMP remain unclear, we consider that their activity is possibly involved in the special digestive movements found in the proximal colon, such as in anti-peristaltic movements (Hukuhara and Neya, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the activity of the ICC-MP is independent of that of the ICC-SMP. In the mouse, ICC-SMP produce plateau-type action potentials which are conducted to circular smooth muscle cells, possibly in an electrotonic manner, to elicit action potentials (Yoneda et al, 2002;Yoneda et al, 2003;Hotta et al, 2007). It was therefore considered that the activity propagated from one type of ICC could not be conducted to other types of ICC, or alternatively the activity propagated from one type of ICC was insufficient to modulate the activity of other types of ICC.…”
Section: Discussionmentioning
confidence: 99%